Dynamic changes in myelin aberrations and oligodendrocyte generation in chronic amyloidosis in mice and men. Issue 2 (22nd October 2012) - Behrendt, Gwendolyn; Baer, Kristin; Buffo, Annalisa; Curtis, Maurice A.; Faull, Richard L.; Rees, Mark I.; Götz, Magdalena; Dimou, Leda
Abstract Myelin loss is frequently observed in human Alzheimer's disease (AD) and may constitute to AD‐related cognitive decline. A potential source to repair myelin defects are the oligodendrocyte progenitor cells (OPCs) present in an adult brain. However, until now, little is known about the reaction of these cells toward amyloid plaque deposition neither in human AD patients nor in the appropriate mouse models. Therefore, we analyzed cells of the oligodendrocyte lineage in a mouse model with chronic plaque deposition (APPPS1 mice) and samples from human patients. In APPPS1 mice defects in myelin integrity and myelin amount were prevalent at 6 months of age but normalized to control levels in 9‐month‐old mice. Concomitantly, we observed an increase in the proliferation and differentiation of OPCs in the APPPS1 mice at this specific time window (6–8 months) implying that improvements in myelin aberrations may result from repair mechanisms mediated by OPCs. However, while we observed a higher number of cells of the oligodendrocyte lineage (Olig2+ cells) in APPPS1 mice, OLIG2+ cells were decreased in number in postmortem human AD cortex. Our data demonstrate that oligodendrocyte progenitors specifically react to amyloid plaque deposition in an AD‐related mouse model as well as in human AD pathology, although with distinct outcomes. Strikingly, possible repair mechanisms from newly generated oligodendrocytes are evident in APPPS1 mice, whereas a similar reaction of oligodendrocyte progenitors seems to be strongly limited in final stages of human AD pathology. © 2012 Wiley Periodicals, Inc.